KOMODIFIKASI DALAM JURNALISME WARGA DI KOMPASIANA.COM (Hubungan Tarik Menarik Antara Kepentingan Media Dan Warga) - Uun Auliaus Sakinah; Riska Firmanila; Adli (Jurnal Ilmu Komunikasi Balayudha, 2021)
Today's citizen journalism has atracted many people. It can be seen from various Medias flatform that provide space for citizen journalism. Although citizen journalism was born from conventional media, the presence of the internet has made this form growing fastly. One of the most important citizen journalisms in Indonesia is Kompasiana.com which is visited by many people per day. The presence of this citizen journalist is used as a commodification by various parties. The media and society use citizen journalism for their respective interests. The media use the community as a commodification of audiences and workers, on the other hand, the community also uses the media as a forum for self-actualization.